Systematic Literature Review (SLR): The Tradition of Dowry in Marriage in Southeast Asia - Musyaffa Amin Ash Shabah (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
This research aims to explore literature that examines the tradition of wedding dowries in Southeast Asia. The method used in this research is a Systematic Literature Review (SLR). Data sampling used Harzing's Publish or Perish and Watase UAKE applications starting from 2013-2023. The selected articles have passed several specified criteria, resulting in a total of 46 articles. The results of this research show that the country that discusses the topic of marriage dowry significantly in Southeast Asia is Indonesia, with a percentage of 70%, followed by Malaysia at 17%, Thailand at 7%, Vietnam at 4%, and the Philippines at 2%. In terms of research themes around wedding dowries, the topic of wedding dowry traditions is the highest topic category in research in Southeast Asia, with a total of 28 studies and a percentage of 60.87%. Likewise, the contextual approach, with a percentage of 21.74% and Fiqh Theory and Islamic Family Law, with a percentage of 10.87%, are the highest categories of research approaches and analytical theories in research on marriage dowries in Southeast Asia.